Wednesday
April 16, 2014

Homework Help: math

Posted by help on Sunday, July 4, 2010 at 7:16pm.

Find y '. y = (2x^3 + 6)(2x^7 - 3)?

Answer this Question

First Name:
School Subject:
Answer:

Related Questions

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...
TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...
Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...
Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3. Okay so I ...
Math(Please help) - For f(x) = 2x-3 and g(x)= 2x^2 find, a) (f + g)(x) = My ...
math - if x is not equal to negative 3/2, (2x^3-x^2-6x)/(2x+3)equals? a. x-2 b. ...
math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x
math - translate and simplify"six less than twice the sum of a number and three...
Pre-Cal - 1)(1-cos^2x)(csc x) ? Is this equal to sec x? 2) Expand: log7 3 sqrt x...
Math - Prove each identity: a) 1-cos^2x=tan^2xcos^2x b) cos^2x + 2sin^2x-1 = sin...

Search
Members